Flexible switching method of control strategy for MMC-HVDC converter based on AC power grid strength - Peng, Maolan; Feng, Lei; Hao, Xiaoyu; Sun, Meihui; Jiang, Wen; Guo, Chunyi (Frontiers in Electronics, 2025)
Modular Multilevel Converter based High Voltage Direct Current (MMC-HVDC) has been widely used in the large-scale transmission of renewable energy sources (RESs). However, the operating conditions of MMC-HVDC system with RESs are complex and variable, making it challenging to apply a single converter control strategy to different operating conditions, which affects the safe and stable operation of the whole system. In this paper, a flexible switching method of control strategies is proposed for MMC-HVDC converter. Firstly, the state-space model of MMC-HVDC under different control strategies is established, and the small signal stability and stable operation ranges under these control strategies are analyzed. Then, according to the proposed control strategy switching principle, a flexible control switching method for MMC-HVDC converter is proposed. This flexible control switching method ensures a smooth switching between different control strategies and causes a minimal disturbance to the overall system. Finally, a simulation model is established on the PSCAD/EMTDC platform, and the feasibility of the flexible control switching strategy for the MMC-HVDC system is verified. The simulation results show that very small disturbance is observed during the control switching and the flexible control switching strategy can effectively maintain the stable operation of MMC-HVDC system under different operating conditions. The proposed flexible control switching method can be activated according to the change of AC grid strength and it will help improve the stable operation of MMC converter.